Coordination chemistry of group 13 monohalides - Vidovic, D; Aldridge, S (2011)
The Group 13 monohalides, EX, are valence isoelectronic with the key textbook diatomic molecules CO and N2; recent advances in synthetic chemistry leading to the isolation of transition metal complexes containing such fragments as ligands are appraised, together with studies of the electronic structure and reactivity of the coordinated molecules. © The Royal Society of Chemistry 2011.